Effective Reading Programs for Middle and High Schools: A Best-Evidence Synthesis - Slavin, Robert E.; Cheung, Alan; Groff, Cynthia; Lake, Cynthia (Reading research quarterly, 2008)
This article systematically reviews research on the achievement outcomes of four types of approaches to improving the reading of middle and high school students: (1) reading curricula, (2) mixed-method models (methods that combine large-and small-group instruction with computer activities), (3) computer-assisted instruction, and (4) instructional-process programs (methods that focus on providing teachers with extensive professional development to implement specific instructional methods). Criteria for inclusion in the study were use of randomized or matched control groups, a study duration of at least 12 weeks, and valid achievement measures that were independent of the experimental treatments. A total of 33 studies met these criteria. The review concludes that programs designed to change daily teaching practices have substantially greater research support than those focused on curriculum or technology alone. Positive achievement effects were found for instructional-process programs, especially for those involving cooperative learning, and for mixed-method programs. The effective approaches provided extensive professional development and significantly affected teaching practices. In contrast, no studies of reading curricula met the inclusion criteria, and the effects of supplementary computer-assisted instruction were small.